Competition between weak quantum measurement and many-body dynamics in ultracold bosonic gases - Kozlowski, W (2016)
Trapping ultracold atoms in optical lattices enabled the study of strongly correlated phenomena in an environment that is far more controllable and tunable than what was possible in condensed matter. Here, we consider coupling these systems to quantised light where the quantum nature of both the optical and matter fields play equally important roles in order to push the boundaries of what is possible in ultracold atomic systems. We show that light can serve as a nondestructive probe of the quantum state of matter. By considering a global measurement we show that it is possible to distinguish a highly delocalised phase like a superfluid from the Bose glass and Mott insulator. We also demonstrate that light scattering reveals not only density correlations, but also matter-field interference. By taking into account the effect of measurement backaction we show that the measurement can efficiently compete with the local atomic dynamics of the quantum gas. This can generate long-range correlations and entanglement which in turn leads to macroscopic multimode oscillations across the whole lattice when the measurement is weak and correlated tunnelling, as well as selective suppression and enhancement of dynamical processes beyond the projective limit of the quantum Zeno effect in the strong measurement regime. We also consider quantum measurement backaction due to the measurement of matter-phase-related variables such as global phase coherence. We show how this unconventional approach opens up new opportunities to affect system evolution and demonstrate how this can lead to a new class of measurement projections thus extending the measurement postulate for the case of strong competition with the system's own evolution.